Review of: Elli Lemonidou (ed.), CENT ANS APRÈS: LA MÉMOIRE DE LA PREMIÈRE GUERRE MONDIALE.ONE HUNDRED YEARS AFTER: THE MEMORY OF THE FIRST WORLD WAR,Athens: École française d’Athènes, 2018, 234 pages. - Rizas, Sotiris (The Historical Review/La Revue Historique, 2020)
.